Relational leadership and its effect on organizational energy (A comparative study in the Rafidain and Rashid banks) - هلال سمر سعدون; سعيد هديل كاظم (Journal of Economics and Administrative Sciences, 2020)
This research aims to test the relationship between "relational leadership as an independent variable and organizational energy as a dependent variable. The current research variables are among the recent and important variables for the development of organizations, and for the purpose of explaining the relationship and influence between the variables, a set of goals has been formulated, including providing the interested and scientific and theoretical information explaining the nature of the variables The research, and the extent to which its causes are reflected in the research sample to increase the interest of the research organization’s organization and make it more appropriate to the required performance in light of a changing environment in Iraq. For this purpose, a number of the most important hypotheses were formulated (there is no significant correlation between the Relational leadership and organizational energy) in both banks (Al-Rafidain and Al-Rasheed). To achieve these assumptions, field research was applied through a comparative study between Al-Rafidain and Al-Rasheed banks. The study was applied to a number of general managers and their assistants, department managers, and people managers. The sample reached (111) director or 55 directors for Al-Rafidain Bank and 56 for Al-Rasheed, statistical methods were used, including the arithmetic mean and deviation. The data were analyzed through a set of statistical programs (SPSS, 23 Amos, PPR 2.16.3). The most prominent findings reached by the researcher were that both Rafidain and Al-Rasheed banks have a good interest in work according to the relational leadership factor, but there is a disparity in results between the two banks and found a significant superiority of the Rafidain Bank on the rationale for both variables any leadership relational and organizational energy, especially in the behavioral side.